Investigation of the effect of supramaximal eccentric contractions on muscle damage and recovery between the dominant and non-dominant arm - A. Yapıcı; H.B. Yalçın (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose: This research aimed to examine the effects of supramaximal eccentric contractions on the damage of muscle and recovery between the dominant and non-dominant arm. The study was participated by ten male volunteer students who do not have any musculoskeletal and metabolic compliant. This research designed as a cross-over type research. Material: Venous blood samples were drawn before the bout, immediately after the bout one min., moreover, at the 6th, 24th, 48th, and 72nd hours after training. Data were analyzed using the SPSS 21.0 statistical software package. After exercise, the non-parametric Wilcoxon Signed Ranks Test was used to decide the dominant and non-dominant arm influence. Statistical significance for all analyses was accepted at p< 0,05. Results: There was a significant statistical difference in the right, and left arm Creatine Kinase (CK) values at the time when exercise start, 48th and 72nd hours (p<0,05). There was no statistically significant difference in right and left arm Lactate Dehydrogenase values after exercise (p>0,05). Conclusions: There was an increase in muscle damage at 24th and 48th hours after supramaximal eccentric exercise, and it was turned back the start level at 72nd hours. While the arm which is non-dominant recovery is faster than the dominant arm.